KOMPARASI KELAYAKAN USAHA PEMBIBITAN CABAI MERAH KERITING (Capsicum annum L.) DENGAN CABAI RAWIT (Capsicum frutescens L.) DI DESA BANYUKUNING KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Bagus Khoirul Anam; Lutfi Aris Sasongko; Renan Subantoro (MEDIAGRO, 2020)
Chili is one of the horticultural commodities that has important economic value for several countries in the world, including Indonesia. So need to be chili seedlingis as one of the important links in chili cultivation. The purpose of research are to determine the total cost, revenue, and income of merah keriting chili seedling and cayenne chili seedling farming, to know the level of R/C on merah keriting chili seedling and cayenne chili seedling farming, and to know the comparison of income levels and R/C on merah keriting chili seedling and cayenne chili seedling farming. Methods of determining location using purposive sampling. Respondents sampling method using the census method. Methods of analysis used the farming feasibility analysis and the analysis of the inferensial parametric (independent samples t-test). From the results of the data analysis of merah keriting chili obtained total cost amounting to Rp.4.606.561, revenue amounting to Rp.10.410.000, and income amounting to Rp.5.803.439 while the cayenne chili total cost amounting to Rp 1.818.830, revenue amounting to Rp.4.394.000, and income amounting to Rp.2.575.170. Value of R/C merah keriting chili seedling amounting to 2.23 while the value of cayenne chili seedling R/C amounting to 2,29. Income comparison of chili seedling farming shows that there are significant difference between the income of merah keriting chili seedling farming with income cayenne chili seedling farming. Comparison of the R/C chili seedling farming shows that value of R/C merah keriting chili and R/C cayenne chili there is no significant difference. Keywords : Seedling, Chili, R/C, Comparative, Bandungan.